1997
DOI: 10.1093/treephys/17.12.747
|View full text |Cite
|
Sign up to set email alerts
|

Estimating stand water use of large mountain ash trees and validation of the sap flow measurement technique

Abstract: Mountain ash (Eucalyptus regnans F.J. Muell.) forest catchments exhibit a strong relationship between stand age and runoff, attributed inter alia to differences in tree water use. However, the tree water use component of the mountain ash forest water balance is poorly quantified. We have used the sap flow technique to obtain estimates of daily water use in large mountain ash trees. First, the sap flow technique was validated by means of an in situ cut tree experiment. Close agreement was obtained between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 20 publications
7
102
4
Order By: Relevance
“…Large radiation ranges were mainly found when daily fluctuations were measured. The diurnal variation in our sap-flow measurements closely followed radiation, similar to patterns found by Dye and Olbrich (1993), Smith et al (1997) and Vertessy et al (1997). However, daily radiation sums showed a narrower range.…”
Section: Discussionsupporting
confidence: 90%
“…Large radiation ranges were mainly found when daily fluctuations were measured. The diurnal variation in our sap-flow measurements closely followed radiation, similar to patterns found by Dye and Olbrich (1993), Smith et al (1997) and Vertessy et al (1997). However, daily radiation sums showed a narrower range.…”
Section: Discussionsupporting
confidence: 90%
“…Estimation of the sapwood area of a tree stand is commonly achieved based on the correlation between growth parameters of the tree (e.g., diameter at breast height, crown size, biomass, leaf area index) and the sapwood area. Hatton and Vertessy's study showed that the area of xylem conducting tissue, DBH, and tree basal area were efficient upscaling parameters [42,43]. However, there are differences of sapwood width and sapwood area among different tree species, even among different individuals of the same tree species, which is influenced by the tree growth status [44,45], site condition [46,47], and tree genetic traits [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The vegetation transpiration was calculated using the cross-sectional area method (Vertessy et al 1995(Vertessy et al , 1997:…”
Section: Calculation Of Vegetation Transpirationmentioning
confidence: 99%
“…At the plant scale, various measurement methods, including weighing lysimeters, ventilated chambers, radioisotopes, stable isotopes and heat balance/heat dissipation methods have been proven to be valuable tools for conducting basic and applied research (Wullschleger et al 1998). Sap flow instruments, the effective techniques to measure plant transpiration (Hatton et al 1995;Vertessy et al 1997), have been used to study the transpiration of Haloxylon ammodendron and Tamarix ramosissima in Taklimakan desert (Xu 2006;Xu et al 2008). At stand scale, the thermal pulse method has been effectively used to measure the stem sap flow of sub-deciduous (Wullschleger et al 2001;Zhang and Gong 2004;Zhang et al 2005).…”
Section: Introductionmentioning
confidence: 99%